Regulating Fe2(MoO4)3 by Au Nanoparticles for Efficient N2 Electroreduction under Ambient Conditions - Yao, Jiaxin; Zhou, Yitong; Yan, Jun‐Min; Jiang, Qing (Advanced energy materials, 2021)
Ammonia, as an important chemical, has played an indispensable role in the fields of fertilizer precursors, fuel, and energy carriers over time. The electrocatalytic nitrogen reduction reaction (eNRR) has attracted extensive attention due to the potential availability of clean energy under mild conditions, while electrochemical catalysts still need further optimization and exploration restricted by the strong chemical bonds of NN. In this work, it is proposed that a small amount of noble metal (Au) modified Fe2(MoO4)3 can serve as active sites in eNRR. Density functional theory calculations reveal that the interaction of Au with Fe2(MoO4)3 reduces the reaction energy of the rate determining step and inhibits the hydrogen evolution reaction, which increase the eNRR activity and selectivity of Au/Fe2(MoO4)3. As expected, according to the 1H nuclear magnetic resonance measurement as the exclusive quantitative detection approach, the as‐prepared Au/Fe2(MoO4)3 achieves outstanding eNRR performance with 7.61 µg h−1 mg−1cat. NH3 production rate and 18.79% Faradaic efficiency at −0.4 V versus reversible hydrogen electrode in 0.2 m Na2SO4 under ambient conditions. Au nanoparticles modified Fe2(MoO4)3 shows a high Faradaic efficiency of 18.79% and NH3 yield rate of 7.61 µg h−1 mg−1cat. Based on the theoretical calculations, the Mo atoms adjacent to Au serve as catalytic centers for reducing the reaction energy of the rate determining step and inhibiting the hydrogen evolution reaction, which accounts for the brilliant nitrogen electroreduction performance of Au/Fe2(MoO4)3.